Enhancing Work Discipline in the General Administration and Finance: The Role of Transformational Leadership - Wardani, Sekar Pramudita; Rahmi, Yaumul (Jurnal Sains Psikologi, 2024)
Work discipline is needed in a company to achieve company targets. The existence of transformational leadership that provides new perspectives and motivation to employees can improve employee work discipline to achieve company targets. This research was conducted to prove that transformational leadership can affect work discipline in general administration and finance employees of Regional Psychiatric Hospital X. The research method used is quantitative correlation, with information collection using a questionnaire. The sample used was 100 general administration and finance employees of Regional Psychiatric Hospital X. The data obtained were then analyzed using a simple regression analysis method. The results obtained from data processing indicate that transformational leadership has a positive (p < .05) and significant influence on work discipline, where work discipline is influenced by 29.2% by variations in transformational leadership. Thus, transformational leadership significantly influences work discipline in general administration and finance employees of Regional Psychiatric Hospital X.